Formulation and Analysis of Patterns in a Score Matrix for Global Sequence Alignment - James Owusu Asare; Justice Kwame Appati; Kwaku Darkwah (International Journal of Mathematics and Mathematical Sciences)
Global sequence alignment is one of the most basic pairwise sequence alignment procedures used in molecular biology to understand the similarity that arises among the structure, function, or evolutionary relationship between two nucleotide sequences. The general algorithm associated with global sequence alignment is the dynamic programming algorithm of Needleman and Wunsch. In this paper, patterns are exploited in the score matrix of the Needleman–Wunsch algorithm. With the help of some examples, the general patterns realized are formulated as new a priori propositions and corollaries that are established for both equal and unequal length comparisons of any two arbitrary sequences.